INVESTIGATION OF THE EFFECTS OF DIFFERENT RETROGRESSION AND RE-AGING PARAMETERS APPLIED TO THE 7075 ALLOY ON THE MICRO-ARC OXIDATION PROCESS - Yilmaz, Mustafa Safa; Ozer, Gokhan; Sahin, Orhan; Karaaslan, Ahmet (WORLD SCIENTIFIC PUBL CO PTE LTD, 2021)
In this paper, retrogression and re-aging (RRA) heat treatment was applied to 7075 aluminum alloy in T6 condition at different times (30 and 90 min) and temperatures (180 degrees C and 240 degrees C). While RRA heat treatments increase the corrosion resistance of the material, it does not harm its mechanical properties. On the other hand, the surface resistance of aluminum is low. Surface modifications are applied to overcome this deficiency. Among these, the micro-arc oxidation (MAO) method increases the corrosion resistance and attains excellent values in surface hardness. To better understand the RRA/MAOrelationship, heat-treated (RRA) samples with four different parameters were coated with the MAO method. In this way, a ceramic oxide coating layer was created on the material surfaces. In order to determine the RRA parameter effect, the MAO process parameters are kept constant (anode voltage (V-a): 500V, cathode voltage (V-k): 300 V, anode voltage open time (t(a)): 300 mu s, cathode voltage open time (t(k)): 200 mu s, frequency: 160 coating with Hz, and process time: 20 min). Surface properties (coating thickness, surface roughness, surface arc duct's structure, etc.), phase analysis (X-ray diffraction (XRD)) and microstructures (coating cross-section studies: distance-dependent hardness, coating/backing material interface character, coating porosity ratio) were examined. XRD analysis showed that the main phase of the coatings is gamma-Al2O3. A coating layer of around 125 mu m was achieved with the growth rate of 6 mu m/min. Surface roughness was between 5.5 mu m and 8 mu m for different RRA parameters. RRA/MAO relation with the characterization made was detailed, and predictions were made for the surface properties of the material (hardness, corrosion resistance, wear, etc.).
Keywords: AA7075-T6-RRA; coating; micro-arc oxidation; tribology; AA7075 ALUMINUM-ALLOY; CORROSION BEHAVIOR; CERAMIC COATINGS; ELECTROLYTE ADDITIVES; MORPHOLOGY; FILMS; Chemistry; Physics